Design and Build of Operational Activities Application of PKP-PK Hang Nadim (KapakNadim) Hang Nadim International Airport Batam - Fajriansyah Setiawan, Reyvaldo; Martadinata, M. Indra; Abdullah, Anton; Sukahir, Sukahir (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Kapak Nadim application is designed and built to support daily operational activities in the ARFF unit of Hang Nadim International Airport Batam. This application allows users to access information related to the world of Airport Rescue and Fire Fighting (ARFF), regulations, materials to increase personnel knowledge, standard operating procedures at work, and operational activity schedules. This application also provides a real-time vehicle maintenance checklist feature that can assist in checking the feasibility and completeness of vehicles with effective and efficient features in 1 (one) platform. In its development, the Research and Development (R&D) method is used with the ADDIE (AnalysisDesign-Develop-Implement Evaluate) instructional design model created by Dick and Carry (1996) with procedures that allow creators to speed up the design process and minimize errors. The problem in this topic is how ARFF personnel can easily access various knowledge in 1 (one) platform, therefore the author makes the KapakNadim application that can be installed on an android smartphone. The final result of this product development is the KapakNadim application which is equipped with 9 (nine) main features.